Mr. Palengke advertisements language as a cultural dimension in the development of a communication campaign using the high and low context cultural framework - Ramiro, Teresa Joselyn V. (2008)
"While there is an enormous amount of literature on the general subject of language as a cultural dimension, very little has been written about how language influences the development of a communication campaign in relation to the High and Low context framework. Thus, this study looks at how language, as a cultural dimension, may influence the development of a communication campaign for a political candidate--particularly Mar Roxas-- and how language becomes important in persuasion as perceived by Filipino voters and the advertising agency and strategists. To be more specific, the discussion evolves on how an advertising agency constructed an image for Mar Roxas as a political condidate in relation to the culture of Filipino voters using the High and Low context framework. It also deals with understanding the dispositions, character of values of Filipino voters in relation to the advertisements of Roxas using the cultural context framework. This study cites the case of "Mr.Palengke" television commercials of Mar Roxas. Accounting for about 60 percent of his media expenditure in the 2004 election, the advertisements serve as case in points. The first ad talks about Mar Roxas as"Mr. Palengke" while the second ad, the "Election ad" or the "political pedigree ad" talks about his image as a Senatorial Candidate in the 2004 National elections. In this study, moreover, the following theories were used: Edward Hall's High and Low Context Framework and the Communication Campaign Model by K.E. Nowak and Karl Warneryd. These theories serve as references for the study drawn from the literature. The researcher used multi-methods in conducting this research. The following research methods were used anmely Focus Group Discussion with One-shot Survey using the Cultural Context Inventory, In-depth Interview, Participant Observation and Textual Analysis. This study shows that the campaign's elements such as the objectives, target audience, strategy, message, communicator, budget and resources are closely interrelated. Thus, when the aim or even the language of a campaign changes, all or some of the other elements in the campaign will change. Furthermore, results show that language is involved in developing a message format- which is verbally related to words, their definitions, use of space, color, music and other sounds, and clothing."